LC-MS/MS characterization of stress degradation products of Gilteritinib and establishment of HPLC method for analysis of process related impurities of Gilteritinib - Katta, Srinivasa Rao; Ramachandra Rao, Immani; Punitha, P; Siva prasad, Thota (Journal of Applied Pharmaceutical Research, 2024)
Background: The current investigation entails the characterization of seven degradation products (DPs) formed in different stress conditions of gilteritinib employing liquid chromatography-tandem mass spectrometry (LC-MS/MS). Methodology: This study developed a stability-indicating reversed-phase high-performance liquid chromatographic (HPLC) method for precisely determining gilteritinib in the presence of its process-related impurities in bulk drug and formulation samples. To explore the stability profile of gilteritinib, it was exposed to forced degradation experiments conducted under various conditions, including acidic, basic, oxidative, photolytic, and thermal stress. These experiments revealed the degradation of gilteritinib under basic, acidic, and photolytic conditions, forming seven distinct DPs. Result: The chromatographic resolution of gilteritinib and its impurities along with DPs was effectively achieved using a Waters Symmetry C18 (250 mm × 4.6 mm, 5 μm) column using equal volumes of solvent A and B (pH 4.5 phosphate buffer and acetonitrile in 25:75 (v/v) as solvent A, acetonitrile and methanol in 75: 25 (v/v) as solvent B) pumped isocratically at 0.7 mL/min and 230 nm wavelength. The method produces an accurate fit calibration curve in 25-175 μg/mL for gilteritinib and LOQ (0.025 μg/mL) – 0.175 μg/mL for its impurities with acceptable precision, accuracy, and recovery. Conclusion: The efficacy of this method was validated through LC-MS/MS, which allowed for the verification of the chemical structures of newly generated degradation products of gilteritinib. Hence, this method is appropriate for the resolution and evaluation of process-related impurities of gilteritinib and can also be applied for evaluating stress degradation products.